The relationship of Ibrahim bin Mahziar Al-Ahwazi with the pure imams, peace be upon them, in the third century AH / ninth century AD - Al-Ukaili, Asaad Odeh Kazem; Al-Rikabi, Wasan Shijaa Najras (Al-Adab Journal, 2023)
The objective of studying the heritage of Ahl al-Bayt, peace be upon them, which their school has stored and preserved from loss by their followers, expresses a comprehensive school of various branches of Islamic knowledge, The geographical area of the followers of Ahl al-Bayt, peace be upon them, and they needed someone to meet their religious needs and be a link between them and their imams, peace be upon them, This system has an effective and very big role in preserving the entity of the righteous community and protecting it from fragmentation and collapse, Ibrahim bin Mahzyar Al-Ahwazi was one of the trusted agents in Ahwaz during the third AH / ninth century AD, Receiving and distributing legal rights, settling disputes, taking over endowments and the affairs of minors who do not have a guardian, Justice or justice is a basic condition for the agent, in addition to his belief and knowledge of the provisions and affairs of Sharia, his political tact and his ability to preserve the secrets of the Imam and his followers from the rulers and their eyes convergent. It was clear from all the results that we reached that Ahwaz was one of the areas that showed love and obedience to the Ahl al-Bayt, peace be upon them, and those who took care of this spot and gave their directions starting with Imam Ali, peace be upon him, all the way to the awaited Imam Mahdi, may God hasten his reappearance, So high that a large number of great scholars and poets who are considered to be the masters of the Shiite sect emerged in Ahwaz, and a large number of narrators and companions of the agents of Ahl al-Bayt, peace be upon them, emerged in the various regions of Ahwaz and they played a role in the procession of Shiism in the entire Islamic world, and Shiite thought still reminds them with all honor And honor.